English Students’ Perceptions Towards The Implementation Of Online Learning During Covid-19 Pandemic - Yan, Rina Anggraini; Ikhsanudin; Eka Fajar Rahmani (Acitya: Journal of Teaching and Education, 2025)
The aim of this study is to achieve one objective. It is to describe the students’ perception toward the implementation of online learning during Covid-19 pandemic. To achieve this objective, a descriptive survey was implemented. It used the theory of descriptive survey by Creswell (2018). The data collected through a questionnaire and the results were presented in percentage. Furthermore, the subject in this researcher was students in Language Education Study Program in Teacher Training and Education Faculty in Universitas Tanjungpura academic year 2022/2023 of batch 2018 until 2021 regular A and PPAPK which consisted of 322 students. The process of data analysis was started by determining the ideal score and the level of student’s perception by percentage formula. As a result, the point of conclusion is concluded. The students’ perception of the implementation of online learning during Covid-19 pandemic was positive perception (70%) and it’s indicated as a high percentage of positive perception. The positive perception includes the effective class management, infrastructure learning absorption, learning activity and improvement of student's accomplishment.